[Retracted] Investigasi Simulasi Numeris dan Eksperimen Proses Springback Berbentuk Cup Silinder pada Lembaran Baja Karbon SPCC - Mulyanto, Bambang; Khaerudini, Deni S. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
THIS ARTICLE HAS BEEN RETRACTED UNDER THE AUTHOR'S REQUEST BECAUSE IT WAS PUBLISHED IN ANOTHER JOURNAL.The sheet metal forming (SMF) process is one of the manufacturing processes that essential and commonly used in the automotive industry. Compared with casting and forging, forming process into the metal sheet obtain several advantages, including lightweight materials and variations in shapes that can be made. One of the challenges in the SMF process is the springback phenomenon, which can cause a deviation in the size of sheet products. The springback occurs due to the reverse force phenomena due to the effect of its elasticity of sheet carbon steel material that has to experience the formation process. Ironing of SPCC sheet metal with a thickness of 0.8 and 1.0 mm is carried out in a pressure of 2.9 MPa with die velocity 60 mm/sec. The experimental data that carried out with a single die on the Cup Silinder sample test showed that the lower the value of ironing, the higher the value of the springback material. Therefore, the springback phenomenon can be reduced 0.03 to 0.07 mm by engineering the ironing process with a range of 0.15 mm